High-performance full-etched fiber-to-chip grating couplers at 3.7-micron wavelength on silicon - Guojiang Yang; Hengtai Xiang; Zhicheng Li; Laiwen Yu; Yuanrong Li; Yuqi Zhao; Guowu Zhang; Jingshu Guo; Yaocheng Shi; Daoxin Dai (APL Photonics)
Mid-infrared (MIR) silicon photonics have attracted great interest for potential applications in on-chip spectroscopy, free-space communication, and remote imaging. Currently, the high-performance and fabrication-friendly fiber-to-chip grating couplers operating at 3–4 μm wavelength band are still desired urgently. Here, we propose an efficient method for designing a 2D subwavelength grating coupler. The few analytical fitting parameters defining the subwavelength grating periods and fill factors in two dimensions enable a high design degree of freedom and a low search space dimension, resulting in high figure-of-merit and fast convergence simultaneously. The developed 3.7 μm grating coupler showcases record-high coupling efficiency both theoretically (−2.2 dB) and experimentally (−4.4 dB) among the 3–4 μm MIR counterparts. This study provides an effective method for designing fiber-to-chip grating couplers, by which the MIR grating couplers with high performance and fabrication ease are developed, thus paving the way for developing high-performance silicon photonic integrated circuits operating in the MIR wavelength band.